Sustainability versus development: Mudanya's war of survival as a liveable city - Zuhal Ozcan; Nevin Turgut Gultekin; Ozlem Dundar (European Regional Science Association (ERSA), 1998)
Sustainable development assumes that the natural and historical resources of a city which constitute to its local characteristics, will not yield to urban and regional pressures. Economies of the advanced capitalist countries are more or less equal and efficient and sustainability can be developed as a criteria but what about the developing countries? Will they sustain their inequalities and inefficiencies? This concept assumes that every settlement had reached to a certain level of development so is far away from all the pressures of growth. But in developing countries such as Turkey, the basic concern is not the sustainability but the survival of local characteristics. Our anxiety is to regain the liveable characteristics of our cities which have already been dismissed and to achieve a certain level of liveability by increasing the quality of life. The most important problem of developing countries is the physical pressure originating from their level of growth not reached to a point of saturation. Mudanya, Turkey, lives this occasion in such a process worth to discuss. The current developments in Mudanya accomplish a striking example to an urban settlement's war in order not to lose its liveability against metropolitan growth. Deterioration of local values has gained speed especially with the planning of this settlement in Bursa Metropolitan Area. These values can be summarized as sea, the productive agricultural lands and cultural property. g The paper will discuss the concept of survivability within the example of Mudanya by conserving/protecting these values.
Keywords: 330